2021
DOI: 10.1016/j.sjbs.2021.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Genus Ziziphus for the treatment of chronic inflammatory diseases

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 107 publications
0
28
0
2
Order By: Relevance
“…T. aphylla is generally safe and harmless to humans. However, inflammation is a significant development in many illnesses [ 64 ]. Consequently, there is a persistent need to learn more about the benefits of natural medications in treating inflammatory diseases to expand our scientific awareness.…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
See 1 more Smart Citation
“…T. aphylla is generally safe and harmless to humans. However, inflammation is a significant development in many illnesses [ 64 ]. Consequently, there is a persistent need to learn more about the benefits of natural medications in treating inflammatory diseases to expand our scientific awareness.…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
“…Traditional medicine and natural products have the potential for developing therapeutics against chronic inflammatory diseases. Many drugs are obtained from these herbs with limited adverse effects or no side-effects [ 64 ]. They are efficient herbal medications and natural antioxidants because they include antidiabetic chemicals, including alkaloids, phenolics, tannins, and flavonoids, reducing glucose absorption in the intestine or improving pancreatic tissue performance by boosting its performance in terms of insulin production [ 113 ].…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
“…Medicinal herbs have been used for ages to produce safe and effective treatments in contemporary and traditional healthcare systems [9][10][11]. The herbal medicines are helpful for the management of sexual dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…However, when inflammation becomes excessive or chronic, it may contribute to the development of several diseases such as diabetes, cardiovascular disease, and cancer [73,74]. Several studies have aimed to explore the reported use of Ziziphus nummularia as an anti-inflammatory agent in traditional medicine [16]. An analysis of the anti-inflammatory activities of Ziziphus nummularia is listed in Table 6.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…There have also been reports on its beneficial role in treating insomnia, anxiety and fever, although these have not yet been supported by scientific proof [14]. The therapeutic value of Ziziphus nummularia was reported by several other reviews, where various biological properties were reported such as its antioxidant, anti-inflammatory, antimicrobial, antiproliferative, hypoglycemic and hypolipidemic activities [4,[15][16][17]. Moreover, numerous phytochemicals have been isolated from various parts of the plant, including tannins, flavonoids, steroids, glycosides, and alkaloids [18].…”
Section: Introductionmentioning
confidence: 99%